(untitled) (Asian Business Research, 2017)
The LOST (Logistification and Standardization Techniques) project research team has already started to build unique technical-mathematical models which can be applied for economic and service processes. This research takes place at Budapest Business School. In this study we would like to reveal mainly the processes of which support the logistical analysis of production flow can be developed. We did not focus on examining the elements of processes, but our main target was the processes of the whole operational system and their relationship to each other. We explored the flowing elements in the system, such as material, data, information and human resource. We analyzed the features and the flowing features of these elements. We determined the limitations and stress of system looking for the problems caused by bottlenecks and uneconomical structure. In the scope of this paper we present what could be a widening opportunity of the future research. By exploring the economic process of the Hungarian Prison Service (hereinafter HPS) we could have an introduction into the financial processes of Hungarian public sector. Due to the independent scope of authority of the institution, the Hungarian public sector’s detailed financial management graph could be created. The purpose of our article is to identify the modules, processes and related materials and to examine their flowing and transformations as well. As this is the first milestone of a long-run project and as a consequence we form a methodology to examine the public sector organizations’ economic processes on high level.